Strategi Pengembangan Usaha Pengolahan Ikan Kering Menurut Ekonomi Islam di Nagari Air Bangis Kecamatan Sungai Beremas Kabupaten Pasaman Barat - Meri Gustiara; Himmatul Khairi (ARZUSIN, 2026)
The development of the dried fish processing business from the perspective of Islamic Economics has received attention in several studies, but research that specifically discusses the integration of SWOT analysis with the principles of Islamic Economics in the context of local businesses remains limited. This study aims to analyze the development strategy of the dried fish processing business in Nagari Air Bangis based on internal and external factors from the perspective of Islamic Economics. This study employed a qualitative approach with a field research design, involving the main business actor as the informant selected through purposive sampling. Data were collected through semi-structured interviews, observation, and documentation, and were then analyzed descriptively and qualitatively through the stages of data reduction, data presentation, and conclusion drawing, and supported by SWOT analysis. The results showed that the dried fish processing business had strengths in the availability of raw materials, the experience of the business actor, and the local workforce, but also faced weaknesses in the form of limited capital, the use of traditional technology, and dependence on weather conditions. The available opportunities included increasing market demand and the development of digital marketing, while the threats faced included fluctuations in fish catches and business competition. The most relevant strategy was the SO (Strengths–Opportunities) strategy, namely utilizing strengths to seize opportunities. These findings contribute to the development of strategic management studies based on SWOT analysis from the perspective of Islamic Economics and broaden understanding of business development grounded in sharia values. The conclusion of this study affirms the importance of integrating business strategies with the principles of Islamic Economics to achieve business sustainability, while also providing theoretical and practical implications for business actors and policymakers and opening opportunities for further studies on the role of technology and sharia financing.